Pendampingan Pembelajaran Reading Di Pondok Pesantren Al Urwatul Wutsqo Jombang - Khudriyah Khudriyah; Nur Munir (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
Reading is very important to master because reading can open a window to the world, especially reading English texts where many important sources of information are written in English. This assistance aims to help students at the al Urwatul Wutsqo Bulurejo Jombang Islamic boarding school to improve their English reading skills. The results of the mentoring were very positive where there was an increase in reading skills with an average reading score of 47.81 before the implementation of QARs and 68.75 afterward. Likewise, from the paired sample test, the t count is greater than the t table (17.073 > 2.1199).